Splenic Injuries atAl-Kadhimiya Teaching Hospital - Hatam, Hikmat A.; Nile, Anees K.; Abdulshaheed, Nahidh A. (AL-Kindy College Medical Journal, 2009)
Background: The spleen is the most common solid organ injured in patients who had sustained abdominal trauma. Such injuries to the spleen represent approximately one quarter of all blunt injuries of the abdominal viscera. Due to its remarkable vasculature and its fragile structure, splenic rupture is the most widespread cause of intra-abdominal hemorrhage. Objective: To assess the magnitude of splenic injury, the management of splenic injury, and to evaluate the postoperative complications. Methods: A prospective study of 57 cases of splenic injury was performed in Al-Kadhimiya Teaching Hospital during the period between the 1st of October 2004 and the 1st of October 2006. Statistical analysis was then performed to identify the causes, management and postoperative complications. Splenic injuries were graded into 5 grades. Results: The highest incidence of splenic injury was recorded in age group s31-40 year. Penetrating injury was much more common than blunt trauma (73.68% versus 26.31%). Fifty patients (87 %) were diagnosed by exploratory laparotomy, ultrasonography in 5 patients (8.77 %), CT scan was positive in 2 patients (3.5 %). Associated injuries were recorded in 41 patients 71.92%. Pulmonary complications were the most frequent complications (18 patients, 31.57 %). Conclusion: Splenic injuries are common surgical problems in Al-Kadhimiya Teaching Hospital. Still there are many difficulties in establishing the diagnosis of the splenic injury with shortage in the new diagnostic modalities especially (CT -Scan, MR1 and even U/S scan) in the emergency situations. In spite of the dangerous post-operative complications of splenectomy, it is still the most commonly performed surgical procedure in cases of splenic injury